HUBUNGAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP N 43 MERANGIN - Dewi Selvia; Sukur (Pendidikan Matematika | STKIP YM Bangko, 2021)
This research is motivated by the low mathematics learning outcomes of students. The purpose of this study was to describe the significant relationship between independent learning and mathematics learning outcomes of class VIII students of SMP N 43 Merangin in the 2019/2020 academic year. This type of research is a research with a quantitative approach while the method used is correlation. The population and research sample were students of Class VIII SMP N 43 Merangin in the 2019/2020 school year which consisted of 4 classes with 117 students. Sampling using the Taro Yamane formula obtained a sample of 54 people. The data analysis technique used by researchers to test the hypothesis using the Product Moment correlation formula because the data is normally distributed, has a linear pattern, so to test the significance using the z test formula. Based on the results of the study showed that the relationship between independent learning and mathematics learning outcomes of students of Class VIII SMP N 43 Merangin with the correlation coefficient r count 0.369 and r table 0.263 or 0.369 > 0.263 while the contribution between variables X and Y was 13.624% and the z test was obtained z hitung 2.687 and it turns out that z count ≥ z table or 2.687 ≥ 2.580, then Ho is rejected and Ha is accepted. This means that there is a significant relationship between independent learning and mathematics learning outcomes of class VIII students of SMP N 43 Merangin in the 2019/2020 academic year